Biomechanical and antibacterial properties of Tobramycin loaded hydroxyapatite coated fixation pins. Issue 7 (17th February 2014) - Sörensen, Jan Henrik; Lilja, Mirjam; Sörensen, Torben Christian; Åstrand, Maria; Procter, Philip; Fuchs, Sabine; Strømme, Maria; Steckel, Hartwig
Abstract The present study investigates the use of nanoporous, biomimetic hydroxyapatite (HA) coatings deposited on TiO2 coated fixation pins as functional implant surfaces for the local release of Tobramycin in order to prevent bacterial colonization. The impact of HA‐coating thickness, coating morphology and biomechanical forces during insertion into synthetic bone on the drug loading and release properties are analyzed. The coatings are shown to exhibit bactericidal effects against Staphylococcusaureus in agar medium for a duration of 6 days after loading by adsorption with Tobramycin for only 5 min at elevated temperature and pressure. Furthermore, high performance liquid chromatography analysis shows a drug release in phosphate buffered saline for 8 days with antibiotic concentration remaining above the minimal inhibitory concentration for S. aureus during the entire release period. Biomechanical insertion tests into synthetic bone and conventional scratch testing demonstrate adhesive strength at the HA/TiO2 interface. Biocompatibility is verified by cell viability tests. Outgrowth endothelial cells, as well as primary osteoblasts, are viable and firmly attached to both HA and TiO2 surfaces. The results presented are encouraging and support the concept of functional HA coatings as local drug delivery vehicles for biomedical applications to treat as well as to prevent post‐surgical infections. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1381–1392, 2014.